Evaluating local wisdom's impact on financial success: social capital in building economic resilience during covid-19 - Ida Bagus Teddy Prianthara; I Wayan Sunia; I Gusti Ayu Wirati Adriati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research examines the factors supporting the success of financial performance based on local wisdom and social capital as a role in building a people's economy during the COVID-19 pandemic. Respondents in this study were Village Credit Institutions (LPD) throughout Bali. The technique of taking respondents in this study uses the Non-Probability Sampling technique with the method used purposive sampling, which means that the respondent's sampling technique is based on specific criteria such as 1) LPD health status, 2) level of capital owned. Calculating the determination of respondents using the Slovin formula with the calculation results of 100 respondents. The data that is processed is primary data through surveys by distributing questionnaires which are then analyzed using Amos Ver.23.0 software with Structural Equation Modeling (SEM) analysis techniques. The results of this study indicate that partially accounting control variables, leadership style, and organizational culture have a significant positive effect on social capital. Other findings include accounting control, leadership style, organizational culture, and social capital having a significant positive effect on financial performance.